Evidence of a systematic underestimation of free sulfur dioxide by the aeration-oxidation method approved by OIV. (15th May 2022) - Cagnasso, I.; Sacco, A.; Petrozziello, M.; Bonello, F.; Asproudi, A.; Giacosa, S.; Rossi, A.M.; Durbiano, F.
Graphical abstract: Highlights: By 591A method an underestimation of free SO2 content in wine simulant is obtained. The most complete work for the uncertainty evaluation of SO2 content in wine to date. By comparing 591A method and gravimetric method the values resulted not consistent. A large results variability was obtained by experiments of specialized laboratories. A harmonization of the procedure for the application of 591A method in wine is needed. Abstract: The aeration-oxidation method stated by the International Organisation of Vine and Wine (OIV) in the Resolution OIV-OENO 591A-2018 is internationally recognized as one of the election technique for free SO2 quantification in wine. The present work highlighted that an underestimation of the SO2 content is obtained by applying this 591A method. A measurement uncertainty evaluation on the basis of the Guide to the Expression of Uncertainty in Measurement and of the Monte Carlo simulations was carried out on a wine simulant solution with a known concentration of free SO2, prepared by gravimetry. By comparison between this 591A and the gravimetric methods, the obtained data resulted to be not consistent. To confirm this underestimation, measurement experiments were conducted by nine specialized laboratories with the 591A method on the same sample and none of which estimated the amount of free SO2 which was present in the wine simulant.